Alley cropping: trees as sources of green-manure and mulch in the tropics - Wilson, G.F.; Kang, B.T.; Mulongoy, K. (1986)
In the development of technologies for improving the efficiency of agriculture, it must be remembered that agricultural systems are ecosystems in which man plays a dominant role in directing the energy flow into food and other material necessary for his survival. Therefore, the efficiency of an agricultural system is determined, to a certain extent, by the level of man's interference or management, and his success in diverting energy in the desired direction. Many tropical systems are inefficient not because of natural resource limitation but because of limited management. For example, a bush fallow system in which the rotation consists of two years cropping followed by eight years naturally regenerated fallow, has management limited to the cropping period or only 20% of the cycle. To correct this discrepancy some form of fallow management must be developed to ensure that more of the energy generated during that period is directed to meeting man's needs. Farmers in the tropics have long realized the efficiency of some trees in restoring soil fertility, and have endeavoured to give these plants selective advantages. In Africa, species such as Acioa bateril, Macrothylum sp., Anthonatha macrophylla and Gliricidia sepium are encouraged and protected during cropping and given a better chance of dominating the fallow (Benneh, 1971; Wilson & Kang, 1981). In Asia, farmers use Leucaena leucocephala and Sesbania grandijlora in the fallow (NAS, 1979). It would be unfair tQ say that researchers have not tried to find suitable fallow species for the humid tropics, but the results have not contributed significantly to food production in the region. The major short-coming has been the emphasis on herbacious species in environments dominated by trees and shrubs. Milsum & Bunting (1928), in suggesting that shrub legumes may be more suitable than herbacious legumes for soil restoration in the humid tropics, pointed out that nitrogen released from decomposing plant tissue could be more important than that exuded from roots in these environments. By taking the above suggestion even further we are now in an era where trees as well as woody shrubs are being hailed as the saviours of the tropics, and are receiving much attention in the drive to improve or develop more efficient alternatives to the bush fallow